2018
DOI: 10.1016/j.celrep.2018.03.104
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Suppresses Cell-Competition-Mediated Apical Elimination of RasV12-Transformed Cells from Epithelial Tissues

Abstract: Recent studies have revealed that newly emerging transformed cells are often eliminated from epithelial tissues via cell competition with the surrounding normal epithelial cells. This cancer preventive phenomenon is termed epithelial defense against cancer (EDAC). However, it remains largely unknown whether and how EDAC is diminished during carcinogenesis. In this study, using a cell competition mouse model, we show that high-fat diet (HFD) feeding substantially attenuates the frequency of apical elimination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 49 publications
7
104
1
Order By: Relevance
“…For instance, it has been shown in mammalian cell culture systems that when Ras-, Src-or ErbB2-transformed cells are surrounded by normal cells, the transformed cells are apically extruded and leave the epithelium [14][15][16][17] . Apical extrusion of transformed cells has been also observed in zebrafish embryos and in various epithelial tissues in mice 15,18,19 . Importantly, when transformed cells alone are present, apical extrusion does not occur, implying that there are certain types of cell-cell communication between normal and transformed cells.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, it has been shown in mammalian cell culture systems that when Ras-, Src-or ErbB2-transformed cells are surrounded by normal cells, the transformed cells are apically extruded and leave the epithelium [14][15][16][17] . Apical extrusion of transformed cells has been also observed in zebrafish embryos and in various epithelial tissues in mice 15,18,19 . Importantly, when transformed cells alone are present, apical extrusion does not occur, implying that there are certain types of cell-cell communication between normal and transformed cells.…”
mentioning
confidence: 89%
“…Red or blue dots indicate genes of which expression is significantly and more than twofold upregulated or downregulated, respectively, in the mix culture with Ras cells. The P value for PTGS2 is 1.8 × 10 recombination events less frequently, resulting in the expression of RasV12 in a mosaic manner within various epithelial tissues 19 . In this study, we focussed on the pancreas, as Ras mutations are frequently observed in human pancreatic cancer.…”
Section: Cox-2 Expression Is Increased In Mix-cultured Normal Cellsmentioning
confidence: 99%
“…Apical extrusion of transformed cells has been also observed in various epithelial tissues in mouse in vivo systems (Kon et al, ; Sasaki et al, ). In addition, environmental factors such as obesity and inflammation profoundly influence the frequency of elimination of transformed cells (Sasaki et al, ). It should be determined whether and how the myosin‐II‐spectrin complex is involved in these processes in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…For example, when oncogenic Ras‐ or Src‐transformed cells are surrounded by normal epithelial cells, transformed cells are apically extruded from the epithelial layer. The apical eradication of transformed cells has been observed in cell culture systems (Hogan et al, ; Kajita et al, ; Leung & Brugge, ; Wu et al, ) as well as in Drosophila (Vidal, Larson, & Cagan, ), zebrafish (Kajita et al, ), and mouse (Kon et al, ; Sasaki et al, ) in vivo. In this process, normal epithelial cells recognize the presence of the neighboring transformed cells and actively eliminate them from epithelia, implying that normal epithelia have antitumor activity that does not involve immune cells, which is termed EDAC (epithelial defense against cancer) (Kajita et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that it is also important to consider the caveola-status of the host epithelium. Apical extrusion has been proposed to represent an early-response mechanism that allows epithelia to eliminate newlytransformed cells from the body, potentially before they have proliferated to any significant degree (Hogan et al, 2009;Kajita and Fujita, 2015;Kajita et al, 2010;Kon et al, 2017;Ohoka et al, 2015;Sasaki et al, 2018). Failure of the epithelium to execute oncogenic extrusion would then be predicted to promote tumor cell retention and potential proliferation.…”
Section: Discussionmentioning
confidence: 99%